Jews and Christians in antiquity (Leuven ; Paris ; Bristol, CT)
iv, 370 sayfa
Keywords: “This volume brings together a selection of papers presented at two conferences on Jewish-Christian interaction in Antiquity held in Leuven and Aix-en-Provence in 2013 and 2014. It aims to introduce a different approach to this crucial topic and some new issues following from this. Specialists of Ancient Judaism, Early Christianity, Patristics, Late Antiquity, Rabbinic Studies, Papyrology, Epigraphy, Hagiography, and Gnosticism have focused on such topics as the consequences of the Jewish wars for the relations between Jews and Christians in Palestina, the cultural and religious exchange between the two communities in Alexandria, Smyrna, Syria, the Jewish-Christian polemics in Rabbinic literature, the papyrological and epigraphic evidences of the Jewish and Christian presence in Egypt and Rome, the coexistence of Jews and Christians in Northern Italy, Hispania, North Africa, Gaul, etc. The papers are arranged chronologically (from the 1st to the 7th century CE) as well as geographically (the Eastern and Western part of the Roman Empire). The volume offers both “general surveys” and “case studies”, each of them exploring different aspects of Jewish-Christian interaction.” --